The Influence of Intuitive Eating on Weight Satisfaction in College Students - Reynolds, Ashley (Curr Dev Nutr, 2021)
OBJECTIVES: The objective was to examine the relationship between intuitive eating behavior and weight satisfaction in college students. METHODS: A cross-sectional convenience sample of college students completed an online survey that evaluated frequency of intuitive eating, weight satisfaction (happy/neutral/upset), and Health-Related Quality of Life (HRQOL). Body mass index (BMI) was calculated using self-reported height and weight. Independent t-tests were used to compare differences in desired weight change, BMI, and days feeling healthy and full of energy between students who identified as an intuitive eater and those who did not. An ANOVA was used to examine differences between weight satisfaction groups and frequency of intuitive eating. RESULTS: Participants (N = 655) were 19.8 ± 1.5 years old, female (63%), and white (84%). College students that identified as intuitive eaters (61%) reported significantly less desire to change their weight than non-intuitive eaters (10.76 ± 11.21 vs. 16.98 ± 13.13, P < 0.01), had a healthier BMI 24.2 ± 4.7 vs. 25.7 ± 5.8, P < 0.01), and reported more days per month (d/m) feeling healthy and full of energy (12.2 ± 8.6 vs. 2.8 ± 7.5, P < 0.001). A main effect of intuitive eating was found for weight satisfaction, (F(1,2) = 49.158, P < 0.001). Individuals who were happy with their current weight reported significantly greater intuitive eating activity than individuals who did not care about their current weight (P < 0.01) and those who were upset about their current weight (P < 0.001). CONCLUSIONS: This data shows that students who identified as eating intuitively reported having a higher body weight satisfaction, a healthier BMI, and reported more d/m feeling healthy and full of energy. This research justifies the need for health programming to focus on encouraging intuitive eating behavior, especially for college students who are at risk for unhealthful diet practices. FUNDING SOURCES: This project was supported by the USDA National Institute of Food and Agriculture, Hatch project number #ME0022104 through the Maine Agricultural & Forest Experiment Station. NJ Agriculture Experiment Station.